Bingkai Pecahan Berbasis MIKIR untuk Meningkatkan Aktivitas Belajar dan Pemahaman Konsep Penjumlahan Pecahan di Sekolah Dasar - Budiyanto Budiyanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The understanding of the concept of adding fractions of grade V SD Negeri Padike II students is low and has not reached the KKM (Minimum Completeness Criteria) that has been set by the school. It can be seen from the number of students as many as 23 people, who have fulfilled the KKM as many as 8 people (34.78%), while 15 people (65.22%) do not meet. This is because during learning, students are not actively involved, starting from experiencing, interacting, communicating, being inspired, and reflecting. So that props are needed that can help them so that they active in the learning process and improve the understanding of the concept of adding fractions. The purpose of this study was to describe the increase in learning activities and understanding of the concept of adding fractions to fifth-grade students of SD Negeri Padike II, Sumenep Regency. This research uses classroom action research methods that aim to improve the quality of learning by describing learning activities and understanding the concept of adding fractions for students through quantitative and qualitative data. The results obtained after applying the MIKIR (Mengalami, Interaksi, Komunikasi, Inspirasi, Refleksi) of students who did not complete were only 4 (17%) and 19 (83%) who completed or exceeded the KKM.